Pelatihan Perhitungan Harga Pokok Produksi dalam Menentukan Harga Jual Produk Pada UMKM Kuliner di Kelurahan Bengkong Sadai Kota Batam - Ita Mustika; Ferdila Ferdila; Khadijah Khadijah; Sumardin Sumardin (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Selling price decisions that are often inappropriate by MSME business actors are caused by their tendency to set selling prices without considering correct calculations and accounting principles, but relying more on their estimates. The purpose of this service activity is to increase the understanding of MSME actors about the calculation of Cost of Goods Produced (COGS) to determine selling prices more precisely. The method used in this activity is through training and direct assistance to business actors to calculate the cost of goods produced by their business and determine the selling price of their products. The evaluation results show an increase in understanding and skills of Culinary MSME actors in Bengkong Sadai Village, Batam City after the implementation of this activity, as seen from the way they now calculate the cost of goods produced before setting the selling price of their products.